Seks Edukasi dalam Pencegahan Pelecehan Seksual pada Remaja - Az Zahra, Atnandia (Pustaka : Jurnal Ilmu-Ilmu Budaya, 2024)
Sexual education is an effort to prevent sexual harassment, especially against children. Sexual education is given to children from an early age as knowledge, guidance and prevention to face things in the future as they get older and to shape character and behavioral patterns so that they are able to avoid behavior that is at risk of sexual harassment or deviant sexual behavior. Sexual harassment can be experienced by both women and men. Sexual harassment is most likely to occur during adolescence, where adolescence is a transition period from childhood to adulthood so curiosity is very high. The role of parents is the most important in sexual education, their role as companions, educators, monitors in their children's sexual matters. The purpose of this journal literature is to provide information about the importance of sex education in preventing sexual harassment in adolescents. This research uses a literature study method for inclusive and non-inclusive journals, as well as a comparison of news source data from the previous year to the present. The research results obtained are the factors that cause sexual harassment, types of sexual harassment, sex education as a form of preventing sexual harassment in teenagers, and and forms of protection for victims of sexual harassment.